2019
DOI: 10.3390/ijms20184452
|View full text |Cite
|
Sign up to set email alerts
|

E-cadherin Downregulation and microRNAs in Sporadic Intestinal-Type Gastric Cancer

Abstract: CDH1 gene, encoding E-cadherin, is a tumor suppressor gene frequently altered in gastric cancers (GCs) of both diffuse (DGC) and intestinal (IGC) histotypes, albeit through different mechanisms. The study aimed to characterize CDH1 expression in sporadic IGC and to investigate whether microRNAs (miRs) are involved in its transcriptional control. We evaluated CDH1 expression by quantitative real-time PCR (RT-qPCR) in 33 IGC patients and found a significant downregulation in tumor tissues compared to normal coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 52 publications
0
22
0
Order By: Relevance
“…The role of cadherins in the process of cancer development has been studied widely over the last decades [ 6 , 10 , 11 , 12 ]. In human medicine, cadherins have been evaluated in many malignancies, such as pancreatic cancer, melanoma, hepatocellular carcinoma, glioblastoma, breast and gastric cancers [ 13 , 14 , 15 , 16 ]. Because most of humans’ solid tumors are of epithelial origin, adhesion molecules at the junctions of epithelial cells and cell signaling pathways are of great interest.…”
Section: Introductionmentioning
confidence: 99%
“…The role of cadherins in the process of cancer development has been studied widely over the last decades [ 6 , 10 , 11 , 12 ]. In human medicine, cadherins have been evaluated in many malignancies, such as pancreatic cancer, melanoma, hepatocellular carcinoma, glioblastoma, breast and gastric cancers [ 13 , 14 , 15 , 16 ]. Because most of humans’ solid tumors are of epithelial origin, adhesion molecules at the junctions of epithelial cells and cell signaling pathways are of great interest.…”
Section: Introductionmentioning
confidence: 99%
“…MiR-101 acts as a tumor suppressor in GC. The expression of miR-101 in GC tissues was significantly decreased compared with adjacent normal tissues [9][10][11]. Dong X et al have proved that miR-101 is an independent prognostic factor for the overall survival of GC patients that correlated with the pathological differentiation degree, lymph node metastasis and depth of infiltration [10].…”
Section: Discussionmentioning
confidence: 99%
“…Dong X et al have proved that the expression of miR-101 in GC tissues is significantly lower than that in cancer-adjacent normal tissues, and miR-101 is an independent prognostic factor affecting the overall survival of GC patients [10]. Rossi T et al have shown that miR-101 is significantly down-regulated in 33 patients with intestinal GC [11]. In addition to that in tumor tissues, the expression of miR-101 in plasma is also a sensitive indicator for GC.…”
mentioning
confidence: 99%
“…18 In addition, loss of miR-26, miR-101, and miR-214 contributes to overexpression of EZH2, leading to the development of digestive cancers. [19][20][21][22][23] Among the abovementioned microRNAs, the effect of miR-26 on EZH2 has been widely noted and has been identified in HCC, CRC, and GC. 19,20,22 Another study identified that EZH2 can also bind to the lncRNA HOX-AS2 together with KDM1A to form a complex implicated in PC cell proliferation, 24 and a similar function can also be performed by the lncRNA HOXA11-AS in GC.…”
Section: Main Modifiers Of Histone Methylation In Digestive Cancers Kmtsmentioning
confidence: 99%